The Synthesis And Characterization Of Group One Metal Titanates And Their Application In Photocatalysis - Rahman, Nur Ruzaina Abdul (2019)
Group one metal titanates has been synthesized via hydrothermal method using group one metal hydroxides. The results show the formation of nanomaterials such as Li-TiO2200oC/12h nanobiscuits (NBs), Na-TiO2200oC/12h nanoribbons (NRs), K-TiO2200oC/12h nanowires (NWs) and Cs-TiO2200oC/12h nanospheres (NSs). The XRD patterns of Li-TiO2200oC/12h, K-TiO2200oC/12h and Cs-TiO2200oC/12h showed the presence of the dominant anatase phase at (101) except for Na-TiO2200oC/12h. This was due to the Na+ ion within the anatase lattice resulting in the distortion of the anatase phases and formation of the sodium titanate phases. This was in agreement with the ICP-OES result which showed the molar ratio of Na/Ti was 0.161 which was higher than K/Ti(0.157) and Li/Ti(0.046) respectively. In addition, the deconvolution of the Na 2p XPS signal showed the presence of peaks at 1071.3 eV and 1070.3 eV corresponding to the Na-O-Ti species. Besides that, controlling the hydrothermal temperature and the duration of synthesis, resulted in changes in the morphology as well as the particle size of the titanates. The Dr-UV/Vis analysis indicated the band gap energy of Li-TiO2200oC/12h, Na-TiO2200oC/12h, K-TiO2200oC/12 and Cs-TiO2200oC/12h to be 3.12, 3.05, 3.07 and 3.17 eV respectively. The surface area of the samples was calculated to be 32.0, 120.0, 155.0 and 24.3m2g-1 for Li-TiO2200oC/12h, Na-TiO2200oC/12h, K-TiO2200oC/12h and Cs-TiO2200oC/12h respectively. Photocatalytic study revealed that Li-TiO2200oC/12h exhibited enhanced photocatalytic efficiency and mineralized MB better compared to Degussa P25 and anatase TiO2.